Preparation method of polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material

By using tanninic acid to modify h-BN nanosheets in epoxy resin and performing in-situ oxidation polymerization under heating conditions, the problem of insufficient thermal conductivity of traditional epoxy resins is solved, and the thermal conductivity and mechanical properties are significantly improved, which is suitable for heat dissipation materials for electronic equipment.

CN119592010APending Publication Date: 2025-03-11ZHEJIANG RONGTAI TECHNOLOGY ENTERPRISE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411171751.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Traditional epoxy resins have shortcomings in thermal conductivity, which is difficult to meet the needs of efficient heat dissipation in modern electronic equipment. Simple physical mixing of h-BN nanosheets with epoxy resin leads to weak bonding between fillers and substrates, reducing thermal conductivity.

Method used

By ultrasonic dispersing and ball milling the hexagonal boron nitride (h-BN) powder with aqueous tanninic acid, tanninic acid modified h-BN nanosheets were prepared and physically mixed with epoxy resin. In situ oxidation polymerization of tanninic acid under heating conditions, forming a polytanninic acid modified h-BN nanosheet/epoxy composite material.

Benefits of technology

It improves the dispersion and interface compatibility of h-BN nanosheets in epoxy resin, significantly improves the thermal conductivity and mechanical properties of epoxy composite materials, and is suitable for heat dissipation materials for electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592010A_ABST
    Figure CN119592010A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of epoxy composite materials, in particular to a preparation method of a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material. A preparation method of a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material comprises the following steps: firstly, performing ultrasonic dispersion and ball milling on hexagonal boron nitride powder in a tannic acid aqueous solution, and performing centrifugal separation and drying on the obtained ball milling solution to obtain a tannic acid modified hexagonal boron nitride nanosheet; dispersing the obtained tannic acid modified hexagonal boron nitride nanosheet in ethanol, adding epoxy resin and a curing agent, stirring and mixing, then carrying out reduced pressure distillation to remove all ethanol, uniformly stirring the obtained mixed solution and an accelerant, pouring into a mold, and heating and curing to obtain the polytannic acid modified hexagonal boron nitride nanosheet / epoxy composite material. According to the epoxy composite material prepared by the invention, the interface bonding strength of the filler and the matrix is high, the thermal conductivity is good, and the epoxy composite material has excellent mechanical properties and is particularly suitable for being used as a heat dissipation device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of epoxy composite materials, and in particular to a method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material. Background Art

[0002] With the continuous improvement of the performance of electronic products, especially the widespread application of high-performance processors, high-power LEDs, integrated circuits and other components, the heat flux density of electronic devices has increased dramatically, which has put forward more stringent requirements for heat dissipation materials. Epoxy resin has become an ideal matrix material in the field of electronic packaging and heat dissipation due to its excellent adhesion, chemical corrosion resistance, good processability and certain mechanical strength. However, traditional epoxy resin has deficiencies in thermal conductivity and is difficult to meet the needs of efficient heat dissipation of modern electronic equipment. By introducing high thermal conductivity fillers (such as metal oxides, carbon materials, ceramic particles, etc.) into the epoxy resin matrix, epoxy resin-based electronic heat dissipation materials with excellent thermal conductivity can be prepared. These fillers form an effective thermal conductive network in the epoxy resin, significantly improving the thermal conductivity of the composite material, enabling it to better dissipate the heat generated by the electronic equipment quickly, ensuring the stable operation of the equipment and extending its service life. Hexagonal boron nitride (h-BN) is a thermal conductive material with excellent electrical insulation properties. Especially after being peeled into h-BN nanosheets, the thermal conductivity is higher and can be widely used in the manufacture of various high thermal conductivity composite materials. It should be pointed out that simply physically mixing h-BN nanosheets with the polymer matrix will lead to uneven distribution of hB nanosheets inside the matrix and weak interface bonding between the filler and the matrix, ultimately reducing the thermal conductivity of the composite material.

[0003] Chinese patent CN110922719A discloses a boron nitride / epoxy resin composite thermal conductive material and its preparation method, which obtains surface-modified h-BN nanosheets after ultrasonic exfoliation and surface modification with a silane coupling agent, and then composites it with epoxy resin. The epoxy composite material prepared by this method has limited improvement in interface compatibility.

[0004] Chinese patent CN113969040A uses hyperbranched polyethylene polymer to perform non-covalent surface modification on h-BN, which effectively improves the dispersibility of h-BN nanofiller and its interfacial compatibility with the epoxy matrix. However, the non-covalent effect makes the binding force between the modified molecules and h-BN weak, and the thermal conductivity and mechanical properties of the obtained epoxy composite material are still not ideal.

[0005] To this end, the inventors provide a method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material. Summary of the invention

[0006] In order to solve the above technical problems, the present application provides a method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material.

[0007] The present application provides a method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material, which is achieved through the following technical solutions: A method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material comprises the following steps: Step 1: adding hexagonal boron nitride (h-BN) powder to tannic acid aqueous solution, ultrasonically dispersing for 1-180 min to obtain h-BN dispersion, then transferring the h-BN dispersion to a ball mill, and ball milling at 200-2500 rpm for 0.5-72 h; Step 2, after the ball milling reaction is completed, the ball milling solution is centrifuged at 500-10000 rpm, and then the separated wet powder is dried at 40-160° C. for 1-48 h to obtain tannic acid modified h-BN nanosheets; Step 3, adding the tannic acid modified h-BN nanosheets obtained in step 2 into ethanol, and ultrasonically dispersing for 1 to 180 minutes to obtain a modified h-BN nanosheet dispersion with a concentration of 5 to 100 mg·mL-1; Step 4, mixing the modified h-BN dispersion obtained in step 3 with the epoxy resin and the curing agent for 0.5 to 24 hours until uniform, and then distilling under reduced pressure at 60° C. for 1 to 48 hours to remove the ethanol solvent; Step 5, stirring and mixing the solution obtained in step 4 with the accelerator at room temperature for 0.1 to 12 h until uniform, and then standing and degassing for 0.1 to 12 h under vacuum. After all bubbles are removed, the obtained mixed solution is poured into a molding mold, and the polytannic acid modified h-BN nanosheet / epoxy composite material is obtained by heating and curing.

[0008] The present application uses the π-π conjugation effect between tannic acid and h-BN to modify the surface of h-BN, thereby improving the dispersibility of h-BN. The tannic acid-modified h-BN nanosheets can be in-situ oxidatively polymerized into polytannic acid inside the epoxy matrix under heating conditions, thereby improving the filler-matrix interface compatibility and ultimately improving the thermal conductivity and mechanical properties of the epoxy composite material.

[0009] Preferably, in the step 1, the dispersion concentration of the hexagonal boron nitride (h-BN) powder in the tannic acid aqueous solution is 0.1 to 100 mg·mL -1 ; The tannic acid concentration in the tannic acid aqueous solution is 0.1~100 mg·mL -1 .

[0010] Preferably, in step 1, the dispersion concentration of hexagonal boron nitride (h-BN) powder in the tannic acid aqueous solution is 5 to 20 mg·mL -1 ; The tannic acid concentration in the tannic acid aqueous solution is 1~4 mg·mL -1 .

[0011] Preferably, the ball mill and grinding balls used in step 1 are made of one of stainless steel, zirconium oxide, silicon carbide, silicon nitride, agate, nylon, and polytetrafluoroethylene; and the diameter of the grinding balls is 1-20 mm.

[0012] Preferably, the BN dispersion obtained in the step 1 is transferred to a zirconia ball mill, and 18-24 zirconia grinding balls are added, and the mixture is ball milled at a rotation speed of 600-1000 rpm for 10-15 hours to obtain a ball mill solution.

[0013] By adopting the above technical scheme, it can be ensured that tannic acid is effectively grafted on the surface of h-BN nanosheets, and the obtained h-BN nanosheets modified with surface grafted tannic acid can be evenly distributed in the epoxy matrix, and the interface compatibility between the h-BN nanosheets modified with surface grafted tannic acid and the epoxy matrix is ​​good, which can improve the thermal conductivity and mechanical properties of epoxy composite materials.

[0014] Preferably, in the step 2, after the ball milling reaction is completed, the ball milling solution is centrifuged at 5000-6500 rpm, and then the separated wet powder is dried at 60-80° C. for 10-12 h to obtain tannic acid modified h-BN nanosheets.

[0015] Preferably, in the step three, the tannic acid modified h-BN nanosheets obtained in the step two are added to ethanol, and ultrasonically dispersed for 20 to 30 min to obtain a modified h-BN nanosheet dispersion with a concentration of 8 to 15 mg·mL-1.

[0016] Preferably, the epoxy resin used in step 4 is E-51 epoxy resin, and the curing agent is methyl hexahydrophthalic anhydride MHHPA; the accelerator used in step 5 is 2,4,6-tris(dimethylaminomethyl)phenol DMP-30.

[0017] Preferably, the mass ratio of the E-51 epoxy resin, methyl hexahydrophthalic anhydride MHHPA, and 2,4,6-tris(dimethylaminomethyl)phenol DMP-30 is 100:(70~100):(0.1~2); in step 5, the thermal curing temperature of the polytannic acid modified h-BN nanosheet / epoxy composite material is 100~160°C.

[0018] Preferably, in the step five, the tannic acid modified h-BN nanosheets account for 10 to 40 wt % of the total mass of the poly-tannic acid modified h-BN nanosheets / epoxy composite material.

[0019] Further preferably, in the step five, the tannic acid modified h-BN nanosheets account for 20 to 25 wt % of the total mass of the poly-tannic acid modified h-BN nanosheets / epoxy composite material.

[0020] The polytannic acid modified h-BN nanosheet / epoxy composite material of the invention has excellent thermal conductivity and mechanical properties, and has a simple preparation process, low cost, is environmentally friendly, is suitable for large-scale production, and can be widely used as a thermal conductive material.

[0021] In summary, this application has the following advantages: 1. The polytannic acid modified h-BN nanosheet / epoxy composite material of the present invention is prepared by dispersing h-BN nanoparticles in a tannic acid aqueous solution, and then subjecting the h-BN nanosheet to a ball milling treatment to obtain a tannic acid modified h-BN nanosheet. The tannic acid modified h-BN nanosheet is then physically mixed with an epoxy resin, and under heating and curing conditions, the tannic acid on the surface of the h-BN is subjected to in-situ oxidative polymerization to obtain a polytannic acid modified h-BN nanosheet / epoxy composite material. The epoxy composite material prepared by the above method has a filler that can be uniformly distributed in a matrix, and the interface compatibility between the filler and the matrix is ​​good, thereby improving the thermal conductivity and mechanical properties of the epoxy composite material.

[0022] 2. The polytannic acid modified h-BN nanosheet / epoxy composite material of the present invention has excellent thermal conductivity and mechanical properties, and has a simple preparation process, low cost, environmental friendliness, suitability for large-scale production, and can be widely used as a thermal conductive material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 : are SEM photos of nanopowders involved in the embodiments of the present invention. Figure A shows BN nanosheets (referred to as BN) obtained by ball milling with a pure water solution; Figure B shows BN nanosheets (referred to as TA-BN) obtained by ball milling with a tannic acid aqueous solution.

[0024] Figure 2 : is the TGA curve of the relevant nanopowder involved in the embodiment of the present invention. Wherein BN is the BN nanosheet obtained by ball milling with a pure aqueous solution; TA-BN is the BN nanosheet obtained by ball milling with a tannic acid aqueous solution. DETAILED DESCRIPTION

[0025] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples. Example

[0026] A method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material comprises the following steps: Step 1: adding hexagonal boron nitride (h-BN) powder to tannic acid aqueous solution, ultrasonically dispersing for 1-180 min to obtain h-BN dispersion, then transferring the h-BN dispersion to a ball mill, and ball milling at 200-2500 rpm for 0.5-72 h; Step 2, after the ball milling reaction is completed, the ball milling solution is centrifuged at 500-10000 rpm, and then the separated wet powder is dried at 40-160° C. for 1-48 h to obtain tannic acid modified h-BN nanosheets; Step 3, adding the tannic acid modified h-BN nanosheets obtained in step 2 into ethanol, and ultrasonically dispersing for 1 to 180 minutes to obtain a modified h-BN nanosheet dispersion with a concentration of 5 to 100 mg·mL-1; Step 4, mixing the modified h-BN dispersion obtained in step 3 with the epoxy resin and the curing agent for 0.5 to 24 hours until uniform, and then distilling under reduced pressure at 60° C. for 1 to 48 hours to remove the ethanol solvent; Step 5, stirring and mixing the solution obtained in step 4 with the accelerator at room temperature for 0.1 to 12 h until uniform, and then standing and degassing for 0.1 to 12 h under vacuum. After all bubbles are removed, the obtained mixed solution is poured into a molding mold, and the polytannic acid modified h-BN nanosheet / epoxy composite material is obtained by heating and curing.

[0027] Preferably, in step 1, the dispersion concentration of hexagonal boron nitride (h-BN) powder in the tannic acid aqueous solution is 0.1 to 100 mg·mL -1 ; The tannic acid concentration in the tannic acid aqueous solution is 0.1~100 mg·mL -1 .

[0028] Further preferably, in step 1, the dispersion concentration of hexagonal boron nitride (h-BN) powder in the tannic acid aqueous solution is 5 to 20 mg·mL -1 ; The tannic acid concentration in the tannic acid aqueous solution is 1~4 mg·mL -1 .

[0029] Preferably, the ball mill and grinding balls used in step 1 are made of one of stainless steel, zirconium oxide, silicon carbide, silicon nitride, agate, nylon, and polytetrafluoroethylene, and the diameter of the grinding balls is 1-20 mm.

[0030] Further preferably, the BN dispersion obtained in step 1 is transferred to a zirconia ball mill, and 18-24 zirconia grinding balls are added, and the mixture is ball milled at a rotation speed of 600-1000 rpm for 10-15 hours to obtain a ball mill solution.

[0031] Preferably, in step 2, after the ball milling reaction is completed, the ball milling solution is centrifuged at 5000-6500 rpm, and then the separated wet powder is dried at 60-80° C. for 10-12 h to obtain tannic acid modified h-BN nanosheets.

[0032] Preferably, in step three, the tannic acid-modified h-BN nanosheets obtained in step two are added to ethanol and ultrasonically dispersed for 20 to 30 min to obtain a modified h-BN nanosheet dispersion with a concentration of 8 to 20 mg·mL-1.

[0033] Preferably, the epoxy resin used in step 4 is E-51 epoxy resin, and the curing agent is methyl hexahydrophthalic anhydride MHHPA; the accelerator used in step 5 is 2,4,6-tris(dimethylaminomethyl)phenol DMP-30; the mass ratio of E-51 epoxy resin, methyl hexahydrophthalic anhydride MHHPA, and 2,4,6-tris(dimethylaminomethyl)phenol DMP-30 is 100:(70~100):(0.1~2).

[0034] Preferably, in step 5, the tannic acid modified h-BN nanosheets account for 10-40wt% of the total mass of the polytannic acid modified h-BN nanosheets / epoxy composite material. Further preferably, in step 5, the tannic acid modified h-BN nanosheets account for 20-25wt% of the total mass of the polytannic acid modified h-BN nanosheets / epoxy composite material.

[0035] Preferably, the thermal curing temperature of the polytannic acid modified h-BN nanosheet / epoxy composite material is 100-160° C. Further preferably, the thermal curing temperature of the polytannic acid modified h-BN nanosheet / epoxy composite material is 115-125° C., and the curing time is 3-5 hours.

[0036] Example 1: A method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material, the steps are as follows: Step 1: Add 1 g of BN powder (Tianyuan Aerospace Materials (Yingkou) Technology Co., Ltd.) to 100 mL of 2 mg·mL-1 tannic acid aqueous solution and ultrasonically disperse for 30 min at an ultrasonic frequency of 40 kHz and an ultrasonic power of 800 W to obtain a BN dispersion. Then, transfer the BN dispersion to a zirconia ball mill and add 20 zirconia grinding balls with a diameter of 5 mm. Mill at a speed of 800 rpm for 12 h to obtain a ball mill solution. Step 2: After the ball milling reaction is completed, the ball milling solution obtained in step 1 is centrifuged at 6000 rpm, and then the separated wet powder is dried at 60° C. for 12 h to obtain tannic acid modified h-BN nanosheets; Step 3, adding the tannic acid modified h-BN nanosheets obtained in step 2 into ethanol, and ultrasonically dispersing for 30 min at an ultrasonic frequency of 40 kHz and an ultrasonic power of 800 W to obtain a modified h-BN nanosheet dispersion with a concentration of 10 mg·mL-1; Step 4, stirring and mixing the modified h-BN dispersion obtained in step 3 with E-51 epoxy resin and MHHPA for 3 h until uniform, the mass ratio of E-51 epoxy resin to MHHPA is 100:80, the mass ratio of the modified h-BN nanosheets contained in the modified h-BN dispersion to the E-51 epoxy resin is 100:45.2, and after stirring and mixing evenly, distilling under reduced pressure at 60° C. for 12 h to remove the ethanol solvent, to obtain an epoxy resin mixed solution; Step 5: Stir and mix the epoxy resin mixture obtained in step 4 with DMP-30 at room temperature for 1 h until uniform, the mass ratio of E-51 epoxy resin, MHHPA, and DMP-30 is 100:80:0.8, and then stand for degassing under vacuum for 2 h. After all bubbles are removed, the defoamed mixed solution is poured into a molding mold, and heated and cured at 120° C. for 4 h to obtain a polytannic acid modified h-BN nanosheet / epoxy composite material. The content of modified h-BN nanosheets in the obtained polytannic acid modified h-BN nanosheet / epoxy composite material is 20wt%.

[0037] The polytannic acid modified h-BN / epoxy composite material is prepared by adding tannic acid modified h-BN nanosheets (TA-BN) to epoxy resin, and then initiating in-situ oxidative polymerization of tannic acid under heating conditions to finally obtain the polytannic acid modified h-BN / epoxy composite material. Therefore, it is necessary to first prepare tannic acid modified h-BN (TA-BN).

[0038] like Figure 1 As shown in A, the h-BN product obtained by ball milling with pure aqueous solution contains a large number of h-BN bulk particles, which indicates that ball milling of h-BN nanoparticles with pure aqueous solution cannot completely convert them into h-BN nanosheets.

[0039] like Figure 1 As shown in Figure B, when ball milled with tannic acid aqueous solution, the h-BN product obtained has a distinct lamellar structure, and almost no h-BN bulk particles are observed, indicating that the h-BN is well exfoliated into h-BN nanosheets.

[0040] In order to determine the thermal stability of tannic acid-modified h-BN nanosheets, thermogravimetric curves were recorded. Figure 2As shown in the figure, the weight loss rate of BN nanosheets (BN) obtained by ball milling in pure water solution is only 1.7% in the whole temperature range (30~800℃), and this small weight loss is mainly caused by the removal of surface adsorbed water and hydroxyl groups. For BN nanosheets (TA-BN) obtained by ball milling in tannic acid aqueous solution, the weight loss reaches 11.9%, which is much higher than BN, which is mainly due to the thermal decomposition of surface tannic acid at high temperature.

[0041] The difference between Example 2 and Example 1 is that: Step 4, the modified h-BN dispersion obtained in Step 3 is stirred and mixed with E-51 epoxy resin and MHHPA for 3 h until uniform, the mass ratio of E-51 epoxy resin to MHHPA is 100:80, the mass ratio of the modified h-BN nanosheets contained in the modified h-BN dispersion to the mass ratio of E-51 epoxy resin is 100:20.1, and after stirring and mixing uniformly, it is distilled under reduced pressure at 60°C for 12 h to remove the ethanol solvent to obtain an epoxy resin mixed solution. The content of modified h-BN nanosheets in the obtained polytannic acid modified h-BN nanosheet / epoxy composite material is 10wt%.

[0042] The difference between Example 3 and Example 1 is that: Step 4, the modified h-BN dispersion obtained in Step 3 is stirred and mixed with E-51 epoxy resin and MHHPA for 3 h until uniform, the mass ratio of E-51 epoxy resin to MHHPA is 100:80, the mass ratio of the modified h-BN nanosheets contained in the modified h-BN dispersion to the mass ratio of E-51 epoxy resin is 100:77.5, and after stirring and mixing uniformly, it is distilled under reduced pressure at 60°C for 12 h to remove the ethanol solvent to obtain an epoxy resin mixed solution. The content of modified h-BN nanosheets in the obtained polytannic acid modified h-BN nanosheet / epoxy composite material is 30wt%.

[0043] The difference between Example 4 and Example 1 is that: Step 4, the modified h-BN dispersion obtained in Step 3 is stirred and mixed with E-51 epoxy resin and MHHPA for 3 h until uniform, the mass ratio of E-51 epoxy resin to MHHPA is 100:80, the mass ratio of the modified h-BN nanosheets contained in the modified h-BN dispersion to the mass ratio of E-51 epoxy resin is 100:120.5, and after stirring and mixing uniformly, it is distilled under reduced pressure at 60°C for 12 h to remove the ethanol solvent to obtain an epoxy resin mixed solution. The content of modified h-BN nanosheets in the obtained polytannic acid modified h-BN nanosheet / epoxy composite material is 40wt%.

[0044] The difference between Example 5 and Example 1 is that: in step 4, the modified h-BN dispersion obtained in step 3 is stirred and mixed with E-51 epoxy resin and MHHPA for 3 h until uniform, the mass ratio of E-51 epoxy resin to MHHPA is 100:80, the mass ratio of the modified h-BN nanosheets contained in the modified h-BN dispersion to the mass ratio of E-51 epoxy resin is 100:9.5, and after stirring and mixing uniformly, it is distilled under reduced pressure at 60°C for 12 h to remove the ethanol solvent to obtain an epoxy resin mixed solution. The content of modified h-BN nanosheets in the obtained polytannic acid modified h-BN nanosheet / epoxy composite material is 5wt%.

[0045] The difference between Example 6 and Example 1 is that: in step three, the tannic acid modified h-BN nanosheets obtained in step two are added to ethanol, ultrasonically dispersed for 30 min, the ultrasonic frequency is 40 kHz, the ultrasonic power is 800 W, and a modified h-BN nanosheet dispersion with a concentration of 20 mg·mL-1 is obtained.

[0046] The difference between Example 7 and Example 1 is that: in step 3, the tannic acid-modified h-BN nanosheets obtained in step 2 are added to the DMSO solution and ultrasonically dispersed for 60 min at an ultrasonic frequency of 40 kHz and an ultrasonic power of 800 W to obtain a concentration of 15 mg mL -1 5 mg·mL -1 The surface grafted modified nano-aramid dispersion was heated to 50°C and reacted under magnetic stirring at 600 rpm for 30 min. The solid powder was filtered under reduced pressure and the surface grafted modified ANF / TA@h-BN powder was obtained after vacuum drying. The surface grafted modified ANF / TA@h-BN powder was added to ethanol and ultrasonically dispersed for 30 min at a frequency of 40 kHz and a power of 800 W to obtain a modified h-BN nanosheet dispersion with a concentration of 10 mg·mL-1.

[0047] Preparation method of surface grafted modified nano-aramid dispersion: first weigh 2.5g of Kevlar49 thread cut into 0.5mm length (DuPont Kevlar49, USA) and put it into a 500mL beaker, add 100mL deionized water and ultrasonicate for 30min, the ultrasonic frequency is 40kHz, the ultrasonic power is 800W, pour out the deionized water and add 50mL ethanol for ultrasonic dispersion for 1h, the ultrasonic frequency is 40kHz, the ultrasonic power is 800W, pour out the ethanol and put the cleaned Kevlar49 Kevlar fiber thread into an electric constant temperature blast drying oven at 60℃ for 1 hour. 2h, dry to remove water and ethanol on the surface; then put it in a vacuum drying oven to evaporate the water completely; weigh 3g potassium hydroxide KOH and put it into an 800mL beaker, put the magnetic rotor and the dried Kevlar49 short silk thread into the 800mL beaker in turn, then add 500mL DMSO, seal it with plastic wrap and paraffin film, put it on a magnetic stirrer and maintain stirring at 25℃ for 7days to obtain a uniform and stable ANFS / DMSO dispersion with a concentration of 5mg / mL; take 25mL of ANFS / DMSO dispersion in a 100mL small beaker, add 30ml Deionized water was added to make the nano-Kevlar fiber ANFS gel precipitate, and then the mixture was stirred at 1000 rpm for 60 min to obtain a uniform mixture. The uniform mixture was vacuum filtered and rinsed with deionized water for 3 times. The solid obtained after filtration was placed in a 100 mL polytetrafluoroethylene hydrothermal autoclave, and 60 mL of HSO4 / HNO3 mixed acid (HSO4 concentration in the mixed acid: 37.5 wt%, HNO3 concentration: 8.75 wt%, HSO4 and HNO3 volume ratio of 3:1) was added at 10 drops / 1 min. The polytetrafluoroethylene hydrothermal autoclave was placed in an oven at 120 ° C for 2 h, and the obtained mixed solution was vacuum filtered and rinsed with deionized water for 3 times. The obtained solid powder is vacuum dried to obtain surface carboxyl modified nano-aramid hANFS; the surface carboxyl modified nano-aramid hANFS is prepared by in situ production of nano silver clusters on the surface carboxyl modified nano-aramid hANFS by a sol-gel method to obtain surface grafted modified nano-aramid, specifically, 0.76 g of silver nitrate was dissolved in 200 mL of distilled water and magnetically stirred at 200 rpm / min for 30 min, then 2 g of surface carboxyl modified nano-aramid hANFS was added, and then 5 wt% ammonia water was added after magnetic stirring at 200 rpm / min for 30 min until Ag was completely precipitated, and then magnetic stirring was continued at 20 rpm / min for 1 h, and then the mixture was allowed to stand for 24 h to obtain AgOH / hANFS binary colloid; the AgOH / hANFS binary colloid was washed three times with distilled water and then filtered to obtain a solid powder, which was placed in a vacuum drying oven at 1 After drying at 25℃ for 12h, the mixture was calcined in a transfer atmosphere tube furnace. In air atmosphere, the mixture was heated to 420℃ at a rate of 15℃ / min and calcined for 4h to obtain AgO / hANFS composite powder. A hydrogen-argon mixture was introduced into the atmosphere tube furnace. The volume ratio of hydrogen to argon in the hydrogen-argon mixture was 1:4. The temperature was maintained at 480℃ for reduction reaction for 4h. The mixture was cooled to room temperature naturally and ball milled at 80rpm for 30min to obtain surface-doped nanosilver hANFS. 2.5g of surface-grafted modified nano-aramid was weighed and dispersed in 500mL of DMSO solution for ultrasonic dispersion for 30min. The ultrasonic frequency was 40kHz and the ultrasonic power was 800W. The concentration was 5 mg·mL. -1 Surface grafted modified nano-aramid dispersion.

[0048] The difference between Comparative Example 1 and Example 1 is that: Step 1, 1 g of BN powder is added to 100 mL of deionized water for ultrasonic dispersion for 30 min, the ultrasonic frequency is 40 kHz, and the ultrasonic power is 800 W to obtain a BN dispersion, and then the BN dispersion is transferred to a zirconia ball mill jar, and 20 zirconia grinding balls with a diameter of 5 mm are added; ball milling is carried out at a speed of 800 rpm for 12 h to obtain a ball milling solution.

[0049] The difference between Comparative Example 2 and Comparative Example 1 is that: in step 4, the modified h-BN dispersion obtained in step 3 is stirred and mixed with E-51 epoxy resin, MHHPA, and tannic acid powder for 3 hours until uniform, the mass ratio of E-51 epoxy resin to MHHPA is 100:80, the mass ratio of the modified h-BN nanosheets contained in the modified h-BN dispersion, the E-51 epoxy resin, and the tannic acid powder is 100:45.2:0.09, and after stirring and mixing evenly, the mixture is distilled under reduced pressure at 60°C for 12 hours to remove the ethanol solvent to obtain an epoxy resin mixture.

[0050] The difference between Comparative Example 3 and Example 1 is that: in step 1, 1 g of BN powder is added to 100 mL of 2 mg·mL-1 tannic acid aqueous solution and ultrasonically dispersed for 30 min at an ultrasonic frequency of 40 kHz and an ultrasonic power of 800 W to obtain a BN dispersion, and then the BN dispersion is mechanically stirred at a speed of 800 rpm for 12 h to obtain a ball-milled solution.

[0051] The difference between Comparative Example 4 and Example 1 is that: in step three, the tannic acid modified h-BN nanosheets obtained in step two are added to ethanol, ultrasonically dispersed for 30 min, the ultrasonic frequency is 40 kHz, the ultrasonic power is 800 W, and a modified h-BN nanosheet dispersion with a concentration of 1 mg·mL-1 is obtained.

[0052] The difference between Comparative Example 5 and Example 1 is that: in step 5, the epoxy resin mixture obtained in step 4 is stirred and mixed with DMP-30 at room temperature for 1 h until uniform, the mass ratio of E-51 epoxy resin, MHHPA, and DMP-30 is 100:80:0.8, and then it is allowed to stand and degas under vacuum for 2 h. After all the bubbles are removed, the defoamed mixed solution is poured into a molding mold, and heated and cured at 80°C for 4 h to obtain a polytannic acid modified h-BN nanosheet / epoxy composite material.

[0053] The difference between Comparative Example 6 and Example 1 is that: in step 5, the epoxy resin mixture obtained in step 4 is stirred and mixed with DMP-30 at room temperature for 1 h until uniform, the mass ratio of E-51 epoxy resin, MHHPA, and DMP-30 is 100:80:0.8, and then it is allowed to stand and degas under vacuum for 2 h. After all the bubbles are removed, the defoamed mixed solution is poured into a molding mold, and heated and cured at 180°C for 4 h to obtain a polytannic acid modified h-BN nanosheet / epoxy composite material.

[0054] The difference between Comparative Example 7 and Example 1 is that the preparation method of the boron nitride nanosheet-epoxy composite material comprises the following steps: Step 1: add h-BN nanosheets into ethanol and perform ultrasonic dispersion for 30 min at an ultrasonic frequency of 40 kHz and an ultrasonic power of 800 W to obtain a h-BN nanosheet dispersion with a concentration of 10 mg·mL-1; Step 4, stirring and mixing the h-BN dispersion obtained in step 3 with E-51 epoxy resin, MHHPA, and tannic acid for 3 h until uniform, the mass ratio of E-51 epoxy resin to MHHPA is 100:80, the mass ratio of the modified h-BN nanosheets contained in the h-BN dispersion to the mass ratio of E-51 epoxy resin and tannic acid powder is 100:45.2:0.09, and after stirring and mixing uniformly, distilling under reduced pressure at 60° C. for 12 h to remove the ethanol solvent, to obtain an epoxy resin mixed solution; Step 5, stirring and mixing the epoxy resin mixture obtained in step 4 with DMP-30 at room temperature for 1 h until uniform, the mass ratio of E-51 epoxy resin, MHHPA, and DMP-30 is 100:80:0.8, and then standing and degassing for 2 h under vacuum. After all bubbles are removed, the defoamed mixed solution is poured into a molding mold, and heated and cured at 120°C for 4 h to obtain an h-BN nanosheet / epoxy composite material.

[0055] Control group: The mass ratio of E-51 epoxy resin, MHHPA, and DMP-30 was 100:80:0.8, and the mixture was evenly mixed and allowed to stand for degassing under vacuum for 2 h. After all the bubbles were removed, the defoamed mixed solution was poured into a molding mold and heated and cured at 120 °C for 4 h to obtain an epoxy composite material.

[0056] Performance test: 1. Thermal conductivity test: Determined in accordance with GB / T 10295-2008 "Determination of steady-state thermal resistance and related properties of insulation materials - heat flow meter method". 2. Tensile strength test: Determined in accordance with GB / T 2567-2021 "Test method for properties of resin castings". 3. Impact strength test method: Determined in accordance with ASTM D256 test method.

[0057] Table 1: Test parameters of epoxy composite materials in Examples 1-7 and Comparative Examples 1-7

[0058] In Comparative Example 1, the h-BN surface is not modified with polytannic acid. The comparison results between Comparative Example 1 and Example 1 show that compared with h-BN not modified with polytannic acid, h-BN modified with polytannic acid has better thermal conductivity and mechanical properties improvement effect on epoxy resin.

[0059] In Comparative Example 2, polytannic acid is added to the epoxy composite material by physical blending. The comparison results between Comparative Example 2 and Example 1 show that compared with adding polytannic acid by physical blending, the in situ polymerization of tannic acid on the h-BN surface into tannic acid has better thermal conductivity and mechanical properties improvement effect on epoxy resin.

[0060] In Comparative Example 3, without ball milling treatment, the h-BN nanoparticles cannot be effectively converted into h-BN nanosheets. The comparison results between Comparative Example 3 and Example 1 show that the h-BN nanosheets modified with polytannic acid have better thermal conductivity and mechanical properties for epoxy resin.

[0061] In Comparative Example 4, the low concentration of tannic acid results in a lower content of polytannic acid on the surface of h-BN. The comparison between Comparative Example 4 and Example 1 shows that increasing the content of polytannic acid on the surface of h-BN can improve the thermal conductivity and mechanical properties of the epoxy resin. In Example 6, the high concentration of tannic acid resulted in a high content of polytannic acid on the surface of h-BN, exceeding the saturation concentration required for complete coverage. The comparison results of Example 6 and Example 1 show that the polytannic acid-modified h-BN obtained by using high concentration tannic acid does not significantly improve the thermal conductivity and mechanical properties of epoxy resin, that is, the concentration of tannic acid-modified nanosheets is replaced by 8-15 mg·mL -1 It is appropriate.

[0062] In Comparative Example 5, low temperature resulted in incomplete in-situ oxidative polymerization of tannic acid and incomplete curing of epoxy resin. Comparison results between Comparative Example 5 and Example 1 showed that incomplete tannic acid oxidation and epoxy resin curing resulted in poor thermal conductivity of the epoxy resin composite material and a significant decrease in mechanical properties.

[0063] In Comparative Example 6, high temperature causes partial degradation of the polytannic acid and epoxy resin obtained by in-situ oxidative polymerization. The comparison results between Comparative Example 6 and Example 1 show that the partial degradation caused by high temperature makes the thermal conductivity of the epoxy resin composite material poor and the mechanical properties drop significantly.

[0064] The comparison results of Comparative Example 7 and Example 1 show that at the same addition ratio, the BN nanosheets modified with polytannic acid have better thermal conductivity and mechanical property improvement effects than commercial h-BN powder.

[0065] The modification principle of the surface-modified h-BN nanosheets of the present invention is: First, under the shear force of the ball milling process, h-BN powder is peeled off into BN nanosheets; at the same time, tannic acid in the solution interacts with h-BN nanosheets to obtain tannic acid-modified BN nanosheets; 2. When the tannic acid-modified h-BN nanosheets are dispersed in the epoxy matrix, the tannic acid on the h-BN surface can undergo in-situ oxidative polymerization under heating to generate polytannic acid at the interface between the epoxy matrix and the h-BN nanosheets, thereby improving the interfacial compatibility between the epoxy matrix and the h-BN nanosheets.

[0066] In summary, the polytannic acid modified h-BN nanosheet / epoxy composite material of the present invention has excellent thermal conductivity and mechanical properties, and has a simple preparation process, low cost, environmental friendliness, suitability for large-scale production, and can be widely used as a thermal conductive material.

[0067] In view of the large number of embodiments of the scheme of the present invention, all components, component contents and process parameters can be determined within the corresponding range according to application requirements. The experimental data of each embodiment is huge and numerous, and it is not suitable to list them one by one here, but the content that needs to be verified in each embodiment and the final conclusions obtained are similar.

[0068] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material, characterized in that: The following steps are involved: Step 1: adding hexagonal boron nitride (h-BN) powder to tannic acid aqueous solution, ultrasonically dispersing for 1-180 min to obtain h-BN dispersion, then transferring the h-BN dispersion to a ball mill, and ball milling at 200-2500 rpm for 0.5-72 h; Step 2, after the ball milling reaction is completed, the ball milling solution is centrifuged at 500-10000 rpm, and then the separated wet powder is dried at 40-160° C. for 1-48 h to obtain tannic acid modified h-BN nanosheets; Step 3, adding the tannic acid modified h-BN nanosheets obtained in step 2 into ethanol, and ultrasonically dispersing for 1 to 180 min to obtain a modified h-BN nanosheet dispersion with a concentration of 5 to 100 mg·mL-1; Step 4, mixing the modified h-BN dispersion obtained in step 3 with the epoxy resin and the curing agent for 0.5 to 24 hours until uniform, and then distilling under reduced pressure at 60° C. for 1 to 48 hours to remove the ethanol solvent; Step 5, stirring and mixing the solution obtained in step 4 with the accelerator at room temperature for 0.1 to 12 h until uniform, and then standing and degassing for 0.1 to 12 h under vacuum. After all bubbles are removed, the obtained mixed solution is poured into a molding mold, and the polytannic acid modified h-BN nanosheet / epoxy composite material is obtained by heating and curing.

2. The method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material according to claim 1, characterized in that: In step 3, the tannic acid-modified h-BN nanosheets obtained in step 2 are added to a DMSO solution and ultrasonically dispersed for 30 to 60 min to obtain a concentration of 10 to 20 mg mL -1 The surface grafted modified h-BN nanosheet dispersion is added with 5-20 mg·mL-1 of surface grafted modified nano-aramid dispersion, the temperature is raised to 45-60°C, and the mixture is reacted for 15-30 min under magnetic stirring at 400-600 rpm, and a solid powder is obtained by filtration under reduced pressure. The obtained solid powder is vacuum dried to obtain surface grafted modified ANF / TA@h-BN powder, and the obtained surface grafted modified ANF / TA@h-BN powder is added to ethanol, and ultrasonically dispersed for 20-80 min to obtain a modified h-BN nanosheet dispersion with a concentration of 10-20 mg·mL-1; the surface grafted modified nano-aramid contained in the surface grafted modified nano-aramid dispersion in the step three is at least one of surface nano-silver modified ANF, surface nano-copper modified ANF, and surface graphene modified ANF.

3. The method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material according to claim 2, characterized in that: In the step 1, the dispersion concentration of hexagonal boron nitride (h-BN) powder in the tannic acid aqueous solution is 5 to 20 mg mL -1 ; The tannic acid concentration in the tannic acid aqueous solution is 1~4 mg·mL -1 .

4. The method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material according to claim 1, characterized in that: The ball mill and grinding balls used in the step 1 are made of one of stainless steel, zirconium oxide, silicon carbide, silicon nitride, agate, nylon, and polytetrafluoroethylene; and the diameter of the grinding balls is 1-20 mm.

5. The method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material according to claim 4, characterized in that: The BN dispersion obtained in the step 1 is transferred to a zirconia ball mill, and 18-24 zirconia grinding balls are added, and the mixture is ball milled at a rotation speed of 600-1000 rpm for 10-15 hours to obtain a ball mill solution.

6. The method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material according to claim 1, characterized in that: In the step 2, after the ball milling reaction is completed, the ball milling solution is centrifuged at 5000-6500 rpm, and then the separated wet powder is dried at 60-80° C. for 10-12 h to obtain tannic acid modified h-BN nanosheets.

7. The method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material according to claim 1, characterized in that: In the step three, the tannic acid modified h-BN nanosheets obtained in the step two are added into ethanol, and ultrasonically dispersed for 20 to 30 minutes to obtain a modified h-BN nanosheet dispersion with a concentration of 8 to 15 mg·mL-1.

8. The method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material according to claim 1, characterized in that: The epoxy resin used in step 4 is E-51 epoxy resin, and the curing agent is methyl hexahydrophthalic anhydride MHHPA; the accelerator used in step 5 is 2,4,6-tris(dimethylaminomethyl)phenol DMP-30.

9. The method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material according to claim 8, characterized in that: The mass ratio of the E-51 epoxy resin, methyl hexahydrophthalic anhydride MHHPA, and 2,4,6-tris(dimethylaminomethyl)phenol DMP-30 is 100:(70-100):(0.1-2); in step 5, the thermal curing temperature of the polytannic acid modified h-BN nanosheet / epoxy composite material is 100-160°C.

10. The method for preparing a polytannic acid modified hexagonal boron nitride nanosheet-epoxy composite material according to claim 1 or 9, characterized in that: In the step 5, the tannic acid modified h-BN nanosheets account for 10 to 40 wt % of the total mass of the polytannic acid modified h-BN nanosheets / epoxy composite material.

Citation Information

Patent Citations

  • High-thermal-conductivity boron nitride / epoxy resin composite material and preparation method and application thereof

    CN110922719A

  • Modified boron nitride / epoxy resin heat-conducting composite material and preparation method thereof

    CN113969040A